Ocena serwisów informacyjnych www gmin turystycznych Dolnego Śląska - Gryszel, Piotr (Lower Silesia tourist communes website service assessment, 2005)
The article presents an assessment of tourist information services offered by the official websites of communes and districts in Lower Silesia region, which perform tourist functions and are of above average tourist attractiveness. There have been presented such features which should be characteristic for any model tourist information service.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1095, s. 217-229